Student Resilience in Higher Education: A Research Trend Analysis: Penelitian - Nor Syamimi Mohamed Adnan; Hazman Hassan; Mohd Azri Mohd Nasaruddin; Mohd Kasturi Nor Abd Aziz; Ari Setiawan (Jurnal Pustaka Cendekia Pendidikan, 2025)
Student resilience has emerged as a critical construct in higher education, particularly in response to increasing academic pressure, mental health challenges, and global disruptions affecting university students. Despite the growing volume of research, a comprehensive overview of the intellectual structure, thematic evolution, and global research patterns in this field remains limited. Therefore, this study aims to systematically examine research trends on student resilience in higher education through a bibliometric analysis. Data were collected using Scopus Advanced Search by applying relevant keywords, including student resilience, academic resilience, higher education, and university students. Following a rigorous screening process, a final dataset of 834 journal articles published between 2015 and 2025 was obtained. Scopus Analyzer was employed to examine publication trends, document distribution, and country contributions, while OpenRefine was used to clean and harmonize bibliographic data to ensure accuracy and consistency. Subsequently, VOSviewer software was utilized to visualize co-authorship networks, keyword co-occurrence patterns, and thematic clusters within the literature. The findings reveal a significant and accelerating growth in publications over the past decade, with a sharp increase observed after 2020, reflecting heightened scholarly attention to student mental health and adaptability, particularly during the COVID-19 pandemic. The United States, the United Kingdom, and Australia emerged as the leading contributors, while keyword co-occurrence analysis identified mental health, stress, academic success, and student well-being as dominant and interconnected research themes. The results also highlight the interdisciplinary nature of student resilience research, spanning educational psychology, health sciences, and pedagogical studies. Overall, this bibliometric analysis provides a comprehensive overview of the knowledge structure and global research landscape of student resilience in higher education, offering valuable insights for researchers, educators, and policymakers, and identifying future directions for advancing resilience-focused research and practice in higher education settings.